Some New Midpoint and Trapezoidal-Type Inequalities for General Convex Functions in q-Calculus - Dafang Zhao; Ghazala Gulshan; Muhammad Aamir Ali; Kamsing Nonlaopon (Mathematics, 2022)
The main objective of this study is to establish two important right q-integral equalities involving a right-quantum derivative with parameter <semantics>m∈[0,1]</semantics>. Then, utilizing these equalities, we derive some new variants for midpoint- and trapezoid-type inequalities for the right-quantum integral via differentiable <semantics>(α,m)</semantics>-convex functions. The fundamental benefit of these inequalities is that they may be transformed into q-midpoint- and q-trapezoid-type inequalities for convex functions, classical midpoint inequalities for convex functions and classical trapezoid-type inequalities for convex functions are transformed without having to prove each one independently. In addition, we present some applications of our results to special means of positive real numbers. It is expected that the ideas and techniques may stimulate further research in this field.